Pengaruh ekspektasi pendapatan dan lingkungan keluarga terhadap minat berwirausaha - Rusydi, Hafidh; Purwa Pamungkas, Heni (Jurnal Paradigma Ekonomika, 2024)
Carrying out entrepreneurial activities is one solution to reduce the country's unemployment rate and can improve the country's economy. In the pre-research conducted by the researchers, students were not very interested in entrepreneurship. In cultivating an entrepreneurial spirit in students, it is necessary to have factors that can influence students' interest in entrepreneurship, one of which is income expectations and family environment. This research aims to explain the influence of income expectations and family environment on students' entrepreneurial interest. This research uses associative research methods with a quantitative approach and multiple linear regression analysis with the help of IBM SPSS version 25 software. The research results show that income expectations and family environment simultaneously influence interest in entrepreneurship. Meanwhile, partially, the results obtained were that income expectations had an influence on students' interest in entrepreneurship, while family environment had no effect on interest in entrepreneurship.